(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This article discusses the role of primary school teachers in society, their love for their profession, and their attention, responsibility, and dedication to students during lessons. Information is provided on the management of the education system, the role of the teacher in increasing the effectiveness of education, the issue of upbringing, and the tasks of the teacher in providing knowledge to students.